Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s12520-022-01568-5
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic and paleoenvironmental reconstructions based on the small vertebrates from the Middle Paleolithic of Hohle Fels Cave, SW Germany

Abstract: In this paper, we analyse the fish and small mammal assemblages from the Middle Paleolithic horizons of Hohle Fels Cave to reconstruct the paleoclimatic and paleoenvironmental conditions faced by the Neanderthal groups who occupied the site. The fish assemblage indicates that the freshwater ecosystem around this site was characterized by a pre-mountain river system with the presence of permanent, oxygen-rich, and cold running waters. The results of the Habitat Weighting Method and the Bioclimatic Model applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…cf anglicus was only found in two sites in Hungary and one in Poland although Eemian dates could not be confirmed. By contrast, S. anglicus appeared in great numbers at the very beginning of the last glaciation during MIS 5d–a in various parts of Europe, such as the Rhone Valley and the Massif Central in France [ 58 ], the Ach Valley in Germany [ 59 ] and the Kraków-Częstochowa Upland of Poland [ 60 ]. This may suggest that the narrow-headed vole survived the Eemian interglacial in several refugia, and therefore their rapid re-colonization of Europe was possible as soon as the climatic cooling offered a suitable environment for its expansion.…”
Section: Discussionmentioning
confidence: 99%
“…cf anglicus was only found in two sites in Hungary and one in Poland although Eemian dates could not be confirmed. By contrast, S. anglicus appeared in great numbers at the very beginning of the last glaciation during MIS 5d–a in various parts of Europe, such as the Rhone Valley and the Massif Central in France [ 58 ], the Ach Valley in Germany [ 59 ] and the Kraków-Częstochowa Upland of Poland [ 60 ]. This may suggest that the narrow-headed vole survived the Eemian interglacial in several refugia, and therefore their rapid re-colonization of Europe was possible as soon as the climatic cooling offered a suitable environment for its expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The third paper (Luzi et al 2022) analyzes together the fish and small mammal assemblages from the Middle Paleolithic levels of Hole Fels Cave (southwestern Germany) to reconstruct the past environmental conditions Neanderthals groups encountered when occupying the site. Applying the bioclimatic model for climatic inferences and the habitat weighting method for environmental inferences, the authors identified two different climatic phases.…”
Section: Middle-upper Paleolithic and Last Neanderthalsmentioning
confidence: 99%